2021
DOI: 10.3390/risks9090156
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management Committee, Auditor Choice and Audit Fees

Abstract: We find that risk management committees and BIG4 audit firms contribute to audit fees. We use observations of 895 companies registered in Indonesia for 2014–2018, and to answer our hypothesis we used ordinary least squares analysis. The results show that BIG4 weakens the relationship between RMC and audit fees. Our study proves that higher demand for audit coverage will occur if there is a risk management committee within the company. As a result, audit fees increase. RMC may demand high-quality external guara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 53 publications
0
1
0
1
Order By: Relevance
“…Regarding the link between audit fees and corporate governance, including the audit outcome, extensive research has been conducted in the private sector, such as the link between audit fees and audit committee effectiveness (Ali, Sing, and Al-Akram 2018), internal auditing (Alzeban and Sawan 2016), fraud (Lee and Ha 2021), risk management (Harymawan et al 2021), and even political connections (Ahmad, Bradbury, and Habib 2022). For the public sector, very few recent studies could be identified.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Regarding the link between audit fees and corporate governance, including the audit outcome, extensive research has been conducted in the private sector, such as the link between audit fees and audit committee effectiveness (Ali, Sing, and Al-Akram 2018), internal auditing (Alzeban and Sawan 2016), fraud (Lee and Ha 2021), risk management (Harymawan et al 2021), and even political connections (Ahmad, Bradbury, and Habib 2022). For the public sector, very few recent studies could be identified.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Several recent studies, including Lau et al (2016), Guan et al (2016), and Griffin et al (2021), have investigated the relationship between earnings management and the school ties of top management, including in Indonesia. For instance, Harymawan et al (2021) found that companies with top executives who have school ties with auditors tend to engage in earnings management practices to artificially inflate their reported earnings. Another study by Oswal et al (2020) examined the impact of school ties between top executives and politicians on earnings management in Indonesia and discovered a positive association between the two.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Berbeda dengan auditor yang memiliki profesionalisme yang rendah, maka seorang auditor akan berpotensi untuk berperilaku disfungsional (mengutamakan kepentingan klien). Penelitian yang dilakukan oleh (Cahyani et al, 2015), (Nasir et al, 2014), (Putri & Suputra, 2013), (Handayani, 2013), serta (Harymawan et al, 2021) menyatakan bahwa profesionalisme berpengaruh positif pada kinerja auditor. Hal ini menunjukan bahwa seorang auditor memiliki profesionalisme tinggi maka semakin besar pula usaha mereka dalam memberikan jasa audit menyebabkan auditor tersebut akan dipercaya dan dapat diandalkan sehingga kinerja auditor akan meningkat.…”
Section: Pengaruh Profesionalisme Terhadap Kinerja Auditorunclassified